Practical Training of Future Industry Specialists on the Basis of the Centers for Applied Qualifications - Tetiana Postoіan (Pedagogical Discourse, 2015)
On the basis of the world positive experience of the of professional training, the system of practical training of specialists of viticulture and winemaking industry of agricultural industrial complex on the basis of Center for Applied Qualifications within the structure of viticulture cluster has been offered.The implementation of practical training on the basis of the center will facilitate the transition to a qualitatively new level of training and retraining of highly skilled workers and specialists, ensuring competitiveness and demand for professionals in the industry market.